Capabilities Approach: Contextualizing Participants' Perspectives on Systems Barriers to Recovery. Issue 4 (1st October 2016) - Petros, Ryan; Solomon, Phyllis; Linz, Sheila J.; DeCesaris, Marissa; Hanrahan, Nancy P.
Abstract: Mental health resources are designed to facilitate recovery for adults with psychiatric disabilities. Two participants of an autovideography intervention described systems barriers to recovery. Researchers employed narrative analysis, guided by the capabilities approach, to evaluate how participants storied their experiences. Participants made meaning from encounters with barriers in ways that oppose the spirit and advancement of recovery while engendering adaptive preferences. Findings indicate that inadequate resources attenuate wellbeing by increasing barriers that actively oppose recovery, and positive reframing of unaccommodating environments reinforces adaptive preferences and incapacity. Adequate resources are essential for successful recovery transformation within the mental health system.